Hubungan antara Dukungan Informasional dengan Kecemasan Perpisahan Akibat Hospitalisasi pada Anak Usia Prasekolah - Adiningsih, Fitri; Yektiningtyastuti,; Purwandari, Haryatiningsih (Jurusan Keperawatan FIKES UNSOED, 2006)
This aim of this study is to evaluate relationship between informational support’s and separation anxiety as an effect of hospitalization to pre-school child which is undergoing hospital care. Cross-sectional design was utilized for this study. Product moment correlation was used to analysis data from 30 respondents at Room Anggrek in RSUD Cilacap for March to May 2005. The result showed that 36, 7% had good informational supports besides 53, 3% respondent had not. Most of respondent had middle level of separation anxiety (53, 3%), followed by high level separation anxiety (43, 3%) and low level separation anxiety (3, 3 %). Product Moment Correlations analysis showed r = -0,582, with p < 0, 05. These showed that there was negative correlation between informational support’s and separation anxiety as an effect of hospitalization to pre-school child. The higher informational support was given the lower separation anxiety level.